Tailored monolith supports for improved ultra-low temperature water-gas shift reaction. Issue 11 (12th August 2021) - Portela, Raquel; Wolf, Patrick; Marinkovic, Jakob M.; Serrano-Lotina, Ana; Riisager, Anders; Haumann, Marco
Abstract : A monolithic γ-Al2 O3 support is developed to scale up the WGS process using the supported ionic liquid-phase concept in a structured reactor. The support-ionic liquid-catalyst system maximizes loading and mechanical resistance while achieving high activity and selectivity. Abstract : Supported ionic liquid-phase (SILP) particulate catalysts consisting of Ru-complexes dissolved in an ionic liquid that is dispersed on a γ-alumina porous substrate facilitate the water-gas shift (WGS) reaction at ultra-low temperatures. In this work, a screening of different ceramic support materials was performed to design a suitable monolithic support to disperse the SILP system with the objective of scaling up the WGS process efficiently. γ-Alumina-rich channeled monoliths were developed with the use of natural clays as binders (10 wt% bentonite and 20 wt% sepiolite) with the following properties: i) high volume of mesopores to maximize the catalyst loading and successfully immobilize the ionic liquid-catalyst system via capillary forces, ii) mechanical resistance to withstand the impregnation process and the reaction operating conditions, and iii) surface chemistry compatible with a highly active and selective phase for WGS. The developed monolithic-SILP catalyst demonstrated high stability and long-term WGS performance at 130 °C with an average steady-state CO conversion of around 30% after 190 h time-on-stream (TOS) and a conversion of 23% after 320 h TOS. Interestingly, the catalyst activity proved essentially unaffected by variation in the water partial pressure during operation due to accumulation of water in the monolith, thus making the system highly durable.